Ethyl-p-methoxycinnamate isolated from kaempferia galanga inhibits inflammation by suppressing interleukin-1, tumor necrosis factor-α, and angiogenesis by blocking endothelial functions (Clinics, 2014)
OBJECTIVE: The present study aimed to investigate the mechanisms underlying the anti-inflammatory and anti-angiogenic effects of ethyl-p-methoxycinnamate isolated from Kaempferia galanga. METHODS: The anti-inflammatory effects of ethyl-p-methoxycinnamate were assessed using the cotton pellet granuloma assay in rats, whereby the levels of interleukin-1 and tumor necrosis factor-α were measured in the animals' blood. In addition, the levels of interleukin, tumor necrosis factor, and nitric oxide were measured in vitro using the human macrophage cell line (U937). The analgesic effects of ethyl-p-methoxycinnamate were assessed by the tail flick assay in rats. The anti-angiogenic effects were evaluated first by the rat aortic ring assay and, subsequently, by assessing the inhibitory effects of ethyl-p-methoxycinnamate on vascular endothelial growth factor, proliferation, migration, and tube formation in human umbilical vein endothelial cells. RESULTS: Ethyl-p-methoxycinnamate strongly inhibited granuloma tissue formation in rats. It prolonged the tail flick time in rats by more than two-fold compared with the control animals. The inhibition of interleukin and tumor necrosis factor by ethyl-p-methoxycinnamate was significant in both in vivo and in vitro models; however, only a moderate inhibition of nitric oxide was observed in macrophages. Furthermore, ethyl-p-methoxycinnamate considerably inhibited microvessel sprouting from the rat aorta. These mechanistic studies showed that ethyl-p-methoxycinnamate strongly inhibited the differentiation and migration of endothelial cells, which was further confirmed by the reduced level of vascular endothelial growth factor. CONCLUSION: Ethyl-p-methoxycinnamate exhibits significant anti-inflammatory potential by inhibiting pro-inflammatory cytokines and angiogenesis, thus inhibiting the main functions of endothelial cells. Thus, ethyl-p-methoxycinnamate could be a promising therapeutic agent for the treatment of inflammatory and angiogenesis-related diseases.